Case report: Can cochlear implant stimulation lead to improved balance even after vestibular neurectomy? - Sluydts, Morgana; De Laet, Chloë; De Coninck, Liesbeth; Blaivie, Catherine; van Dinther, Joost J. S.; Offeciers, Erwin; Wuyts, Floris L.; Zarowski, Andrzej (Frontiers in Neurology, 2023)
Introduction: In a previous manuscript from our research group, the concept of vestibular costimulation was investigated in adult subjects that received a cochlear implant (CI). Despite what literature reports state, no signs of vestibular co-stimulation could be observed. Results: In this case report it was described how a woman, who previously underwent a vestibular neurectomy on the left and suffers from bilateral vestibulopathy (BVP), reported improved balance whenever her CI on the left was stimulating. Unexpectedly the sway analyses during posturography indeed showed a clinically relevant improvement when the CI was activated. Discussion: Vestibular co-stimulation as a side effect of CI stimulation could not be the explanation in this case due to the ipsilateral vestibular neurectomy. It is more likely that the results can be attributed to the electrically restored auditory input, which serves as an external reference for maintaining balance and spatial orientation. In addition, this patient experienced disturbing tinnitus whenever her CI was deactivated. It is thus plausible that the tinnitus increased her cognitive load, which was already increased because of the BVP, leading to an increased imbalance in the absence of CI stimulation.